2014
DOI: 10.1002/ppap.201300185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Catalyst Deactivation on Kinetics of Plasma-Catalysis for Methanol Decomposition

Abstract: The effect of catalyst deactivation in the plasma catalysis of methanol decomposition is investigated. A dielectric barrier discharge is generated in the Cu/ZnO/g-Al 2 O 3 catalyst-packed bed reactor. Methanol conversion and generation of CO/CO 2 and HC species using the fresh and deactivated catalyst are compared. Catalyst deactivation usually causes a reduction in the synergetic effect of the plasma and catalyst, mainly as a result of changes in the relative generation of primary radicals by the plasma and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It was also demonstrated that the presence of a catalyst within a plasma discharge resulted in a synergistic effect and was improving VOCs and by-products conversion. Various publications and reviews give detailed reports on non thermal plasma (NTP) coupled to catalysis on VOCs removal such as trichloroethylene [8,[11][12][13], benzene [8,[14][15][16], toluene [8,17,18], isopropanol [19][20][21] and methanol [22][23][24][25]. In particular, a significant attention has been brought on manganese oxide based catalysts, owing to their capacities to store oxygen and activate ozone [11,16,17,19,[25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that the presence of a catalyst within a plasma discharge resulted in a synergistic effect and was improving VOCs and by-products conversion. Various publications and reviews give detailed reports on non thermal plasma (NTP) coupled to catalysis on VOCs removal such as trichloroethylene [8,[11][12][13], benzene [8,[14][15][16], toluene [8,17,18], isopropanol [19][20][21] and methanol [22][23][24][25]. In particular, a significant attention has been brought on manganese oxide based catalysts, owing to their capacities to store oxygen and activate ozone [11,16,17,19,[25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Several plausible hypotheses have been suggested in the literature to account for the enhanced C–H activation using plasma–catalyst combinations: (1) gas-phase electron impact-regulated hydrocarbon dissociation caused by the plasma, , (2) the generation of increased temperature catalytic sites, , (3) the direct interaction between active metal surfaces and the plasma, ,,, and (4) packed-bed effects due to enhanced electric fields from the use of porous dielectric materials. ,,, However, although these postulations have been previously suggested, there are only a few reports that have explored the relative contributions of these phenomena to plasma-driven C–H activation assisted by catalysts. ,,, …”
mentioning
confidence: 99%
“…Additionally, we evaluated the effect of porous dielectric materials (such as the γ-Al 2 O 3 support or SiO 2 diluent) on the activation of CH 4 at elevated temperatures. ,,, It has been detailed in previous reports that porous dielectric materials can enhance the electric field in a DBD via the confinement of charged species within the pores and could thereby facilitate various chemical conversions. ,,, Thus, we performed an additional control run using only the porous support subjected to a calcination and reduction condition identical to that used to generate the 20Ni. In contrast to the DBD only run, no geometric change in the Lissajous curves to the oval shape was observed throughout these experiments (Figure S4).…”
mentioning
confidence: 99%
“…Temperature above 900 K is required to initiate the N2O decomposition. Meantime, direct plasma and plasma assisted catalysis methods are claimed as an efficient method to decompose the N2O with oxygen free systems at room temperature while using nitrogen or argon as the plasma gases [ 236,237,238,239,240,241].…”
Section: Decomposition Of Nitrous Oxide (N2o)mentioning
confidence: 99%
“…Lee et al successfully decomposed N2O by plasma assisted catalytic method [240]. They used a tubular quartz reactor in which the Ru catalyst was supported on Al pellets.…”
Section: Decomposition Of Nitrous Oxide (N2o)mentioning
confidence: 99%